2017
DOI: 10.4103/ijmm.ijmm_17_180
|View full text |Cite
|
Sign up to set email alerts
|

Aetiological Study of Viruses Causing Acute Encephalitis Syndrome in North West India

Abstract: AES occurred sporadically in Rajasthan, samples should be tested first for herpes group of viruses followed by EV or/and for arboviruses depending on season or measles, mumps and RVs in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Japanese encephalitis with Dengue, Japanese encephalitis with tubercular, Japanese encephalitis with Mumps and Japanese encephalitis with Scrub typhus. This is similar to study by Jain P, et al, where mixed infections were found in 12 patients and study by Tiwari JK, et al, which showed multiple etiology in 9 patients [12,7]. Hence in tropical countries endemic diseases and multiple etiologies can be considered.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Japanese encephalitis with Dengue, Japanese encephalitis with tubercular, Japanese encephalitis with Mumps and Japanese encephalitis with Scrub typhus. This is similar to study by Jain P, et al, where mixed infections were found in 12 patients and study by Tiwari JK, et al, which showed multiple etiology in 9 patients [12,7]. Hence in tropical countries endemic diseases and multiple etiologies can be considered.…”
Section: Discussionsupporting
confidence: 90%
“…In this study we observed that 21% of cases were having microbiologically confirmed viral etiology. This was similar to the study done by Tiwari JK, et al, from Rajasthan who studied 3088 patients of all age group and viral etiology was confirmed in 22.7% cases [7]. Other studies also documented almost similar percentage of viral causes which includes 17.2 % in study by Rathore SK, et [8][9][10][11].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Viral meningitis is usually caused by enteroviruses or herpes simplex virus type 2 (HSV-2) [8], whereas a specific etiology of encephalitis had been documented in only 30.4% of cases [9]. In one of the largest Indian studies including both adults and children by Tiwari et al [10], virus identification (serologically or by molecular testing) was possible in 22.7% of acute encephalitis syndrome (AES). The most common virus identified in AES suspects in their study was HSV (8.4%), followed by Epstein Barr virus (EBV) (5.6%), VZV (3.1%), Cytomegalovirus (CMV) (2.2%), Enterovirus (EV) (1.0%), Mumps virus (MPV) (0.9%), Dengue virus (DV) (0.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Viruses have been mainly attributed to be the cause of AES in India though other microbes and toxins have been reported over the past few decades. [1][2][3][4][5][6][7] Noninfective causes of acute encephalitic presentation are increasingly being recognized worldwide. 8 Various infective and noninfective etiologies of AES have been tabulated in Table 1.…”
Section: Causes /Etiologymentioning
confidence: 99%